Legal Review of Government Policy in Granting Coal, Gold and Nickel Mining Permits in Indonesia - Ayuk Suryaningsih (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
Articles 20, 21, 22, 23, 24, 25, and Article 26 concerning WPR and Articles 66-73 concerning IPR from Law no. 4/2009 on Resource and Coal Mining contains implicit rules for craft mining. To achieve peace in society, we use practical methods to resolve conflicts. People's mining, which is an option for conventional mining, is a very real occurrence. Pre-existing issues will be investigated using standard legal study methods. This study will focus on the part of the law that was amended in 2009 that regulates the extraction of minerals and coal, Minerba Law no. 4. Various types of complementary legal documents, such as books and scholarly articles on the topic, can be found in the library's collection. The findings of this study include, first, the city government no longer has the authority to issue permits after the ratification of the Minerba Law in 2020. The government is now responsible for coordinating permits as a whole. Second, if smallholder mining actually occurs, it is not clear who has the authority to designate smallholder mining zones. Third, a culture of bureaucratization will develop in smallholder mining administration as a result of the loss of the strategic role of local governments and their current status as an extension of the central government. Currently, local governments have no powers of their own beyond what has been granted to them by the federal government. Every aspect of mining - from initial exploration to post-mining environmental management (reclamation) and protection of labor health and safety - falls under the purview of the federal government. The sole purpose of local government is to facilitate central cooperation efforts.